Pembuatan Karbon Aktif Dari Limbah Pelepah Kelapa Sawit (Elaies Guineesis Jacq.) Sebagai Media Peyerapan Ion Logam Fe Air Sumur Menggunakan Aktivator Asam Fosfat (H3PO4) - Andriansyah, Ricky; Elwina, Elwina; Suryani, Suryani (Jurnal Riset, Inovasi, Teknologi & Terapan, 2023)
Oil palm (elaies) is a tropical plant that is widely found in Indonesia. The increasing production of this plant has an impact on the increasing amount of oil palm frond waste every year. During this time, the community only utilizes the fruit for the manufacture of CPO while the fronds are discarded and become waste. Palm frond waste contains constituent components in the form of cellulose and lignin so that it has the potential to be utilized as an adsorbent. The manufacture of activated carbon is carried out with the stages of carbonization and activation using H3PO4. The finished activated carbon was then tested for moisture content, ash content, and iodine absorption according to SNI 06-3730-1995, functional group analysis testing with Fourier Transform Infra Red FTIR and Fe metal ion absorption test in well water using an AAS spectrophotometer. From these tests, 7% moisture content, 4% ash content and 909.45 mg/gr iodine absorption were obtained. FT-IR testing obtained 11 fungal groups and Fe metal absorption using an AAS spectrophotometer obtained 77%, so it can be concluded that the activated carbon made is in accordance with SNI 06-3730-1995 specifications